The impact of exercise and athletic training on vascular structure and function - Churchill, T. W. (Current Treatment Options in Cardiovascular Medicine, 2020)
Purpose of review: Myocardial adaptation to athletics and exercise training is a well-described process that has garnered much interest over the past decades. By contrast, our understanding of how the vascular system adapts in the trained athlete remains limited. The goal of this review is to provide a comprehensive overview of the impact of exercise on structure and function of the extra-cardiac vascular system. Recent findings: While structural changes in the size of the aorta are rare in young athletes, emerging data suggest that long-term athletic participation may be a risk factor for aortic dilation in middle-age and beyond. In addition, new findings show that even modest amounts of athletic training such as participation in an individual`s first marathon can have important salutary effects on vascular health. Summary: Vascular adaptations represent an important part of the athletic phenotype and likely play an important role in the overall cardiovascular health of the trained athlete.